Multidrug-Resistance and Biofilm Formation among Acinetobacter baumannii Isolated from Clinical Specimens - Yadav, Poonam; Shyam Kumar Mishra; Shrestha, Sreska; Sah , Ranjit; Rai, Junu Richhinbung; Kattel, Hari Prasad; Sharma, Sangita; Willcox, Mark (Journal of Nepal Health Research Council, 2025)
Background: Acinetobacter baumannii has emerged as a problematic pathogen due to its ability to become resistant to antibiotics and form biofilms. The aim of this study was to explore antibiotic resistance and biofilm formation, and examine any correlation between these in Acinetobacter baumannii isolates.Methods: This was a cross-sectional study conducted at the 750-bed Tribhuvan University Teaching Hospital in Nepal. Identification and antibiotic sensitivity of Acinetobacter baumannii isolates were performed following American Society for Microbiology guidelines. Different β-lactamases were detected by standard phenotypic tests. The microtiter plate method was used to screen strains of their ability to form biofilms. Results: Out of total 18,343 clinical samples processed, 4,249 (23.1%) showed bacterial growth. A. baumannii comprised of 4.7% of the total bacterial growth. Multidrug-resistant (MDR) was exhibited by 97.5% of Acinetobacter baumannii isolates. All multidrug-resistant Acinetobacter baumannii isolates were resistant to cephalosporins and carbapenems; however, they were sensitive to polymyxins. Only few isolates showed sensitivity to sulbactam-containing antibiotics (15.4-29.2%), fluoroquinolones (1.0-7.2%), aminoglycosides (2.6-5.6%), and cotrimoxazole (4.1%). Extended-spectrum-beta-lactamase (ESBL), metallo-beta-lactamase (MBL), Klebsiella pneumoniae carbapenemase (KPC) and AmpC production were found in 54.9%, 73.3%, 41.5% and 14.9% isolates, respectively. Among all tested isolates, 192 were able to produce biofilms, with 83.1% being classified as strong biofilm producers. Those strains that were resistant to gentamicin were more likely to produce biofilms (P<0.05). ESBL, MBL, KPC and AmpC were seen in 51.8%, 71.6%, 43.8% and 16.0% of strong biofilm producers respectively. Conclusions:  Only polymyxins were effective against Acinetobacter baumannii. Carbapenemase producers were generally strong biofilm producers, and gentamicin resistant strains were more likely to produce biofilms. The findings of this study may help to understand antibiotic-resistance mechanisms and provide valuable information in the treatment of MDR Acinetobacter baumannii infections.Keywords: Acinetobacter baumannii, biofilm, carbapenemase; multidrug-resistant.